Implementasi Hot Work Permit sebagai Upaya Pencegahan Kecelakaan di Proyek Jaringan Distribusi Utama SPAM Wosusokas Segmen 3 - Arham Hanif Febria; Iik Sartika; Nur Ani; Wartini Wartini (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Wosusokas SPAM Main Distribution Network Project Segment 3 PT PP-Selaras Join Operation involves various work activities, one of which hot work activities that have high potential fire hazards. During project implementation period, 11 near miss incidents and 25 cases Non-Conformity were recorded in hot work. This study examine implementation hot work permit system effort to prevent work accidents. Study used qualitative descriptive approach with data collection techniques through indepth interviews, observation, and documentation. Subjects this study consisted 6 informants. The object this study was implementation hot work permits at PT PP-Selaras Join Operation. Data analysis was carried out through reduction, presentation, and drawing conclusions. Data validity tested using triangulation sources and methods. Implementation hot work permit carried determining work area through field assessment covering activities such welding, cutting, and grinding. Preparation stage included initial coordination, preparation work methods and JSA, hazard control. Permit valid for 12 hours after validation, but hampered by limited gas testing, number of supervisors, and size of the work area. Hot work permit process has been running well, indicated by the placement documents on permit board, permit extension, supervision, suspension, and emergency handling. Completion hot work permit after work area declared safe through final inspection, closure validation, and permit storage. Implementation of hot work permits on project has been running well through systematic stages, optimization implementation hot work permits can through digitalization of work permits and addition supervisory personnel to ensure all work areas undergo gas testing to minimize potential hazards.